Tree Composition On Light Intensity In Agroforestry Systems In People's Forests - Marti Winarni; Anang Susanto (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2024)
Developing an agroforestry system with conventional community forest plants has several obstacles, such as altitude, temperature, humidity, availability of nutrients, and light intensity, causing forest plants not to grow optimally. Agroforestry is one way to overcome problems on land, one of which needs more light intensity for the growth of forest plants. This research aims to determine optimal sunlight for developing forest plants using an agroforestry system. This research was carried out in the community forest area of Magetan Regency. The survey method used in community forest areas was by taking samples of 6 stand structure compositions and 6 plots in six villages. The parameters observed included the number of branches, crown diameter, plant type, height, and light intensity. Light intensity is measured using a lux meter placed under the canopy. The research results showed that the tree composition Albizzia+Mahagoni+Tectona+Mangifera let of light at 12.01, while the lowest was the tree with the composition Mahagoni+Tectona+ Tamarindus sp+ Gmelina sp.